Pengembangan Website Berbasis Masalah Sebagai Media Pembelajaran untuk Mendukung Pembelajaran Online Pada Materi Laju Reaksi - Crisye Efendi Tambunan; Noven Zakarias Simanjuntak; Nora Susanti (Jurnal Inovasi Pembelajaran Kimia (Journal Of Innovation in Chemistry Education), 2021)
This study aims to determine the feasibility aspect of a problem learning-based website as a learning medium to support online learning on the reaction rate material developed based on BSNP standards. This research consists of three stages, namely the stage of needs analysis based on interviews, observation through goole forms, analysis of learning media and literature study. The development stage begins with compiling a media design, developing, assessing the feasibility of website graphics with the BSNP instrument by one Computer Science lecturer who gets an average score of 3.77 which means very feasible, and assessing the reaction rate material integrated into the website by 3 people Physical Chemistry lecturers and 1 Chemistry teacher get an average content feasibility score of 3.44 which means very feasible, language feasibility of 3.63 means very feasible, and presentation feasibility of 3.66 means very feasible.